Low Profile Planar Inverted-L Antenna (PILA) for UHF RFID Tag on Signal Absorption and Reflection Surfaces - Minh-Tan Nguyen; Yi-Fang Lin; Chien-Hung Chen; Hoang-Son Luong; Hua-Ming Chen (IEEE Access)
In this study, we propose a novel design incorporating six Planar Inverted-L Antennas (PILAs) to miniaturize Ultra-High Frequency Radio Frequency Identification (UHF-RFID) tags, thereby enhancing tag efficiency when mounted on various conductive surfaces. The design enables effective tag antenna operation when attached to surfaces with varying signal absorption and reflection characteristics, obviating the need for a complete antenna redesign. By dominating the capacitive reactance between gaps or the inductive reactance of vias, the tag matches the proposed antenna and the microchip (with an impedance of 10.7–j $134.5~Ω $ at 915 MHz). Both simulation and measurement results confirm the effectiveness of our approach. With this configuration of six adjacent coupled PILA antennas, the proposed tag minimizes electromagnetic field absorption from surfaces, such as containers filled with water or the human body, while enhancing radiation from reflective surfaces like metal. The tag antenna was fabricated on a single FR4 substrate, measuring $30× 20× 3.2$ mm3 ( $0.10~λ _{0} × 0.08~λ _{0} × 0.01~λ _{0}$ ), and successfully tested on various conductive materials. In a free-space medium, a reader antenna with an Effective Isotropic Radiated Power (EIRP) of 4.0 W achieved maximum reading distances of 7.8 m, 6.1 m, and 5.3 m as the tag antenna was positioned on a metal plane, a water-filled container, and on a human body, respectively.